Observation of self‐assembled layers of alkyl phosphonic acid on aluminum using low‐voltage scanning electron microscopy and AFM. (10th January 2013) - Sato, H.; Fujii, T.; Tsuji, E.; Aoki, Y.; Shimizu, K.; Skeldon, P.; Thompson, G.E.; Habazaki, H.
<x xml:space="preserve">Abstract</x> Self‐assembled alkyl phosphate layers have been formed on a flat, anodized aluminum substrate in dilute ethanol solution containing 2 wt% n‐tetradecylphosphonic acid (TDP) and examined by low‐voltage scanning electron microscopy as well as atomic force microscopy and X‐ray photoelectron spectroscopy. Locally, multi‐layered alkyl phosphate films have been formed on aluminum, being clearly observed by a low‐voltage scanning electron microscope operated at less than 1 kV. Atomic force microscopy observations disclosed that bilayers of tetradecylphosphonic acid are stacked on the substrate to form multilayers. The present study revealed that the uniform self‐organized monolayer is not always formed readily on an oxidized aluminum surface. Copyright © 2013 John Wiley & Sons, Ltd.